2000
DOI: 10.1093/ps/79.7.1009
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Tibial Dyschondroplasia

Abstract: Tibial dyschondroplasia (TD) is a skeletal deformity associated with rapid growth in a number of avian species. The disease is the result of a disruption in the cascade of events that occur in the epiphyseal growth plate. Whereas the incidence of TD is susceptible to genetic selection, no specific genetic defect has been identified. Although there are extensive data describing the morphological and biochemical characteristics of the lesion, the mechanism of lesion formation is unknown. However, naturally occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 35 publications
2
26
0
10
Order By: Relevance
“…There was no effect of the bedding type/material, sex and genetic strain on the prevalence of tibial dyschondroplasia. The frequency of TDL and TDR was low, which are similar to those found in the literature (Rath et al, 1998;Praul et al 2000;Almeida Paz et al, 2005;Almeida Paz et al, 2009). The experiment with litter of reused wood shavings presented an increase in lesions of RC and LC.…”
Section: Resultssupporting
confidence: 89%
“…There was no effect of the bedding type/material, sex and genetic strain on the prevalence of tibial dyschondroplasia. The frequency of TDL and TDR was low, which are similar to those found in the literature (Rath et al, 1998;Praul et al 2000;Almeida Paz et al, 2005;Almeida Paz et al, 2009). The experiment with litter of reused wood shavings presented an increase in lesions of RC and LC.…”
Section: Resultssupporting
confidence: 89%
“…This is in broad agreement with other reviews noting that rapid early growth is involved in the development of TD (Orth and Cook, 1994;Praul et al, 2000;Leach and MonsonegoOrnan, 2007). These findings are also in agreement with Shim and Pesti (2011), where increased leg weaknesses were associated with a longer sojourn of the chick in the hatcher.…”
supporting
confidence: 92%
“…There is suggestive information regarding the contribution of incubation to the syndrome (Yalçin et al, 2007;Shim and Pesti, 2011) but there are also many studies showing links to nutritional factors of the chick involving calcium, phosphorus, sodium, potassium, chloride and trace elements (Rennie et al, 1993;Praul et al, 2000;Genin et al, 2008;Thorp, 2008;Oviedo-Rondón and Wineland, 2012). A recent study has shown the effect of high incubation temperature on chick growth plate development (Oznurlu et al, 2016), which may thus have implications for developmental bone diseases such as TD.…”
Section: Incubation and Tibial Dyschondroplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…The mycotoxin fusachromanone and the dithiocarbamates thiram and disulfuram can experimentally induce severe TD lesions (Rath et al, 2005). Previous studies have reported abnormal gene expression in lesioned growth plate cartilage from late stages of TD, based on immunohistochemistry, semi-quantitative real-time reverse transcriptase Á polymerase chain reaction (PCR) and in situ hybridization (Praul et al, 2000;Shirley et al, 2003;Webster et al, 2003). Genes encoding extracellular matrix molecules such as aggrecan, type II collagen, type X collagen, osteopontin and osteonectin, growth factors and hormones such as transforming growth factor-beta, PTH-related peptide and Indian Hedgehog genes, and enzymes such as carbonic anhydrase II (CA2) and matrix metalloproteinase were among those abnormally expressed (Chen et al, 1993;Knopov et al, 1995;Twal et al, 1996;Wu et al, 1996;Rath et al, 1997;Pines et al, 1998;Ben-Bassat et al, 1999;Webster et al, 2003).…”
Section: Introductionmentioning
confidence: 99%